Broadcast talk: the talk strategies - Lee, Siew Chin (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2004)
In broadcast, message is the penultimate product, and language is one of the medium that carries meanings across to the audience. Therefore, a broadcaster uses language as his tool of trade, strategising to maximise the impact of his message. However, different forms of broadcast programmes have different framework, and calls for different types of talk strategies. This paper poses an approach towards defining language use in broadcast; one that looks at the generic construct behind the types of broadcast programmes, the content and talk goals. Derived from an eclectic mix of three different models of defining talk programmes, this paper attempts to describe the talk strategies of a talk programme produced in English by a television station in Malaysia, TV . In the analysis, the writer has found that the talk strategies include roles and identities adopted by the hosts, and how the talk is structured into the programme framework.